ANALISIS KELAYAKAN PENGEMBANGAN USAHA TERNAK KAMBING PERAH (Kasus : Peternakan Prima Fit, Kecamatan Ciampea, Kabupaten Bogor) - Triana Gita Dewi; Narni Farmayanti (Forum Agribisnis, 2011)
Phenomena of excess demand need to be solved by developing dairy goat farming in Indonesia. Prima Fit is one of the farms that conduct a business development of dairy goat farming in 2010. This study was conducted to analyze the feasibility of dairy goat business development and determine the change in some variables. The result of non-financial aspects of the analysis states that according to the market aspect, technical production, management and legal, social, economic and cultural, as well as the environment, business is feasible for conducted either without development or with development. On the financial aspect criteria such as NPV, IRR, Net B/C, and the payback period state that business is feasible for conducting either without development or with development. Result of switching value and sensitivity analysis show that business without development is more sensitive to a decrease in price of milk goat, decrease in quantity of milk goat production, and increase in price of dregs of the tempeh than business with development.